ANTHROPOMETRIC MEASURES OF PRE-ADOLESCENTS INDIAN AND NON-INDIAN (Fiep Bulletin - online, 2013)
The cultural adjustment of the Indians of Dourados Villages causes overweight in their pre-adolescents, when compared to the non-Indians, is the question that created the problematic which has been stipulated to run this study, guided by the general objective of verifying whether there is significant difference between Indians and non-Indian pre-adolescents, in relation to the variables weight, height, diameter, circumference and skin folds, in a sample comprised of 50 pre-adolescents Indians from municipal schools, in the Indian villages of Dourados, Mato Grosso do Sul, and 50 non-Indians also from municipal schools of Dourados City, aged between 6 and 12 years old, respectively. The sort of sampling utilized is the probabilistic, and the data of the variables were tabulated and analyzed by descriptive or exploratory techniques of statistic analysis. The hypothesis was tested through the Test t of Student, and ?2 for the variables of category. The average weight of non-Indians is 75.77lbs (34.37 Kg) and for Indians is 72.86lbs (33.05 Kg). This difference did not present statistical significance by the Test t of student, (t = 1,26; p = 0,21). The height average of (98) non-Indians is 1.41m and the Indians' is 1.39 m. Concerning the differences of height measures, the test (t = 1.45; p = 0.149) has (98) demonstrated not significant. As for the circumferences of the pre-adolescents, the average of the arms measures is 21.84 cm, took from non-Indians, and 21.42 cm, from Indians; the values for abdomen are 63.87 cm (non-Indians) and 65.57 cm (Indians); gluteus, 71.66 cm, of non-Indians, and 70.31 cm, of Indians; legs, 39.80 cm, non-Indians, and 39.91, Indians. The result of the Test t of Student did not show statistical significance to any of these measures. It may be asserted that the fat percentage of the tricipital and subscapular skin folds is significantly higher (t = 2, 109; p = 0,038) in non-Indians, by comparing with the Indian ethnos and concerning (90) the masculine genre it was significant (t = 2, 977; p = 0,005), but in relation to the feminine genre, it was not significant (t = 1,094; p (41) (48) = 0,280). The option for the probabilistic sampling has somewhat hindered the identification of over-weighted pre-adolescents in both ethnic groups, once it was observed at the schools drafted, during the visits, a noticeable number of students clearly over-weighted. That is why a broader study should be done in the schools, by the very teachers of Physical Education, at the beginning and at the end of the school year, as suggestion of monitoring the students' growth.
Keywords: Anthropometric Measures; Pre-adolescents; Indians and non-Indians